Intra-arterial Infusion of Autologous Bone Marrow Mononuclear Stem Cells in Subacute Ischemic Stroke Patients - Ghali, Azza Abass; Yousef, Mohamed Khalil; Ragab, Osama AbdAllah; ElZamarany, Enas Arafa (Frontiers in Neurology, 2016)
Introduction Based on many preclinical and small clinical trials, stem cells can help stroke patient with the possibility of replacing the cells and supporting the remaining cells. The aim of this study was to evaluate the safety and feasibility of bone marrow mononuclear (BMMN) stem cell transplantation in subacute ischemic stroke patients. Materials and methods Thirty-nine (n = 39) patients with subacute ischemic cerebral infarct due to large artery occlusion in the middle cerebral artery (MCA) territory were recruited. They were distributed into two groups: first group (n = 21) served as an experimental group, which received intra-arterial (IA) mononuclear stem cells (bone marrow-derived mononuclear cell), while the other group (n = 18) served as a control group. All the patients were evaluated clinically by National Institutes of Health Stroke Scale, modified Rankin Scale, Barthel Index, modified and standardized Arabic version of the Comprehensive Aphasia Test, and radiological for 12 months. Results The stem cell-treated group showed better improvement, but it was not significant when compared with the non-treated group. The volume of infarction changes at the end of the study was non-significant between both the groups. There was no, or minimal, adverse reactions in stem cell-treated group. Conclusion The study results suggest that autologous BMMN stem cell IA transplantation in subacute MCA ischemic stroke patients is safe with very minimal hazards, but no significant improvement of motor, language disturbance, or infarction volume was detected in stem cell-treated group compared with the non-treated group.